Instructional Package Development of Tie-Dye Based on Creative Economy Concept for Grade 8 Students - Wimolsiri Kuntatum,; Wittaya Worapun, (Journal of Educational Issues, 2024)
The purposes of the study were: 1) to investigate the effects of an instructional package of tie-dye on grade 8 students’ creative thinking, 2) to investigate the effects of an instructional package of tie-dye on grade 8 students’ learning achievement, and 3) to study students’ satisfaction with the instructional package of tie-dye. The participants were 40 grade 8 students in the Thai context selected using the cluster random sampling method. The instruments were an instructional package of tie-dye on grade 8 students’ creative thinking, a creative thinking evaluation form, a learning achievement test, and a satisfaction questionnaire. The statistics used in data analysis were percentage, mean score, standard deviation, a pair samples t-test, and effectiveness index. The results demonstrate the usefulness of the instructional package in fostering the growth of creative thinking and academic accomplishment among the participants. Moreover, product satisfaction could also be reported. The results of the study could illustrate how the creative economy concept benefits art-related subjects and students’ creativity.